The Effects of a Virtual Reality Tourism Experience on Tourist’s Cultural Dissemination Behavior - Yanfang Zeng; Lihua Liu; Rui Xu (Tourism and Hospitality, 2022)
Virtual reality technology has been widely applied in the tourism industry, but the literature examining the relationship between the virtual tourism experience and cultural dissemination behavior is limited. This present study examines how a virtual reality tourism experience could stimulate tourists’ cultural dissemination behavior intention. It does so by developing a moderated mediation model to explore how virtual reality tourism uses digital technology to improve tourists’ experiential value, enhances their pride, and then affects their cultural dissemination behavior intentions. Results derived from a sample of 359 respondents show that VR experiential value can stimulate tourists’ cultural dissemination behavior and that the link between VR experiential value and tourists’ cultural dissemination behavior is mediated by pride. Furthermore, the cultural value of individual collectivism moderates the relationship between VR experiential value and pride. This study extends the theoretical understanding of virtual reality tourism from the emotional perspective and also has practical implications for VR design and destination marketing.